2021
DOI: 10.1111/jav.02736
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fat mass affect the motivation to migrate in northern wheatears

Abstract: To fuel their migratory endurance flights, most birds accumulate large quantities of fat prior to departure. It therefore seems logical that the decision to depart on a migratory flight depends on fuel stores, at least to some extent; very small fuel stores prohibit migratory endurance flight. However, studies linking migrants' estimated fuel stores (or sometimes actual fat stores) to departure likelihood or to migratory restlessness measured in captive birds (an accurate proxy for migrants' motivation to depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…accumulating energy stores. By that, we ensured that all birds carried sufficient and comparable energy stores important for high motivation to resume migration, as many studies have shown a significant positive correlation between energy stores and departure probability ( Schmaljohann et al, 2022 ; Schmaljohann and Eikenaar, 2017 ; Klinner et al, 2020 ; Eikenaar et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…accumulating energy stores. By that, we ensured that all birds carried sufficient and comparable energy stores important for high motivation to resume migration, as many studies have shown a significant positive correlation between energy stores and departure probability ( Schmaljohann et al, 2022 ; Schmaljohann and Eikenaar, 2017 ; Klinner et al, 2020 ; Eikenaar et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…refuelling on energy stores. By that, we ensured that all birds carried sufficient and comparable energy stores important for high motivation to resume migration, as many studies have shown a significant positive correlation between energy stores and departure probability (Schmaljohann and Eikenaar 2017; Klinner et al 2020; Eikenaar, Karwinkel, and Hessler 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Departure decisions have two temporal scales, day‐to‐day and within‐night (Müller et al, 2016 ), and both are directly linked to the routing decision (Schmaljohann & Naef‐Daenzer, 2011 ). Notably, birds adjust their migratory decisions based on intrinsic factors, for example, energy stores (Deppe et al, 2015 ; Eikenaar et al, 2016 , 2021 ; Goymann et al, 2010 ; Schmaljohann et al, 2013 ) and immune function (Brust, Eikenaar, et al, 2022 ; Hegemann et al, 2018 ), and react to extrinsic conditions such as weather (Brust et al, 2019 ; Klinner & Schmaljohann, 2020 ; Schmaljohann et al, 2017 ) and ecological barriers (Deppe et al, 2015 ; Sandberg & Moore, 1996 ; Smolinsky et al, 2013 ). As birds en route constantly react to changing environmental conditions, spatial and temporal migration patterns can be highly flexible among and within individuals (Åkesson & Helm, 2020 ; Stanley et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%